An Initial Performance Analysis of Persistent Memory Allocators - Munoz, Catalina; Honorio, Bruno; Bastelli, Lucas; Francesquini, Emilio; Baldassin, Alexandro (Anais da Escola Regional de Alto Desempenho de São Paulo (ERAD-SP); 2023: Anais da XIV Escola Regional de Alto Desempenho de São PauloDO - 10.5753/eradsp.2023.232673, 2023)
Persistent Memory (PM) has recently resurfaced with the advent of new technologies that make it a competitive option in terms of performance compared to traditional storage, adding the benefit of durability. Because it is byte-addressable, the use of PM is similar to that of volatile RAM (DRAM). However, there are some differences related to data consistency and read/write latency, which makes it necessary to have special memory allocators. This paper presents an initial performance analysis of the impact of two persistent memory allocators, PMDK and Ralloc, using three typical data structures, namely, i) Linked List, ii) Skip List, and iii) Hash Map. Although the study is in its initial phase, we could observe the impact of PM allocator in performance.